Determinan Koefisien Respon Laba (Earnings Response Coefficient-ERC) pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2022 - Prasetyo Panji Pramudya; Rina Trisnawati (STIE Amkop Makassar, 2024)
Profit information significantly impacts corporate performance, serving as the primary focus for viewers of financial reports. Companies frequently encounter factors that impact their responses to the disclosure of earnings information. The objective of this study is to assess the impact of company growth, leverage, information asymmetry, systematic risk, and dividend payout ratio on the profit response coefficient of manufacturing companies in the food and beverage sector that are listed on the BEI from 2018 to 2022. The sample was selected using a purposive selection strategy, yielding a total of 17 companies and 71 data observations. Data testing employs the utilization of several techniques in multiple regression analysis. The research findings indicate that variables such as corporate growth, leverage, systematic risk, and dividend payout ratio have no impact on the earnings response coefficient. The variable of information asymmetry affects the coefficient of earnings response.